The Role of Environmental Accounting in Supporting Efficient Production in Industrial Companies: Exploratory Study in the Eyes of Industrial Companies in Sulaimani - عارف أحمد, شيلان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study aims to evaluate the impact of production processes, specifically the negative effects on the environment that result from these processes, to address these effects by using cleaner production technology as one of the prevention techniques to enhance environmental performance. Cleaner production technology is among the modern management accounting techniques, as it emerged as a result of developments that occurred in the field of business management, as well as a result of increased environmental awareness in general. Cleaner production technology works to protect the environment by reducing pollution from its sources, which contributes to reducing the negative impact on the environment, improving production efficiency, and helping in producing products according to the principle of prevention, as this technology aims to use industrial production and energy in a way that increases competitiveness in the long term and reduces Effectively from polluting the environment. Due to the difficulty of obtaining the necessary data that allows the application of research in industrial companies, the researcher relied on the use of a questionnaire form in a sample of cement and iron companies in the city of Sulaymaniyah. 50 questionnaires were distributed and 43 questionnaires were suitable for analysis. She conducted the study of the questionnaire data through the statistical software SPSS V24. The research reached a set of results, the most important of which is that the problem of environmental pollution is considered one of the fundamental problems with a negative impact, and the risks it causes among workers in companies must be known. The research recommended the need to pay attention to cleaner production in industrial companies in the city of Sulaymaniyah in order to preserve the environment and environmental safety.